Académie Internationale des Sciences et Techniques du Sport (AiSTS)
The International Academy of Sports Science and Technology is a multi-field high education and research centre in Lausanne, Olympic Capital. The main objective of AiSTS is to create a pool of multi-field expertise in the domain of sports education and research. The AISTS, therefore, attempts to develop and apply all sorts of knowledge to the study of sports in connection with biology, medicine, technology, laws, economy, logistics, management, sociology, to name a few. This objective relies on the following three academic pillars: continuing education, postgraduate education and research.